Weigh-in time affects hydration status and acute weight gain in combat sports: A comparison of judo and wrestling (Revista de Artes Marciales Asiáticas, 2021)
This study aimed to investigate the effect of weigh-in time on hydration status and acute weight gain (AWG). Twenty-seven men judo athletes and 23 men wrestlers voluntarily participated in this study. Body mass and urine specific gravity (USG) of the athletes were measured just before official weigh-in and competition. Two-way analysis of variance (split-plot ANOVA) with repeated measurements (time x sport) were used to determine differences in AWG and USG between groups and measurement times. In case of significant difference between sports, t-tests were applied. There was a significant main effect of time (p